PERGAULAN SEKS BEBAS DI KALANGAN MILENIAL DAN SOLUSINYA DALAM PERSPEKTIF HADIS - Saputra, Doni; Almunadi, Almunadi; Nadhiran, Hedhri (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2023)
Adolescence can be described as a phase of someone whose a big curiosity of manythings, and behind this curiosity, there is such a great desire in everything, suchas sex. Nowdays, some people consider that youthness and free sex are two thingshard to be be separated. As known, there are things recommended in Islam insteadof having harmful free sex, namely marriage or fasting. This study uses qualitativeresearch by library research, with primary data refered to authentic hadith books,Sahih Al-Bukhori and Muslim. The study concludes that free sex among millennialyouth is now commonplace due to the uncontrolled development of information flowsand misuse of technology. However, The Prophet SAW had provided a solusion sothat everyone can avoid such evil deed, by getting married or fasting. Specifically,the meaning of fasting (shaum) can be understood contextually in the present daysby doing positive things as a means of managing lust so that one can not be losecontrol of it.